MANAJEMEN MUTU BERBASIS KURIKULUM BERBASIS CINTA (KBC) DALAM MENINGKATKAN BUDAYA MUTU MADRASAH - Andika Papriono; Siti Julaiha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines quality management based on the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) in improving the quality culture of madrasahs. The study is motivated by the need to strengthen quality culture as an effort to enhance educational quality that is not only oriented toward academic achievement but also toward character development, human values, and a humanistic learning environment. The Love-Based Curriculum (KBC), introduced by the Ministry of Religious Affairs of the Republic of Indonesia, emphasizes the values of love, compassion, empathy, respect for human dignity, and social responsibility as the foundation of educational management. The objective of this study is to analyze the role of KBC-based quality management in building and enhancing the quality culture of madrasahs. This research employs a qualitative descriptive approach using a literature review method. Data were collected from books, scientific journals, policy documents, and other relevant academic sources concerning educational quality management, quality culture, and the Love-Based Curriculum. The data were analyzed using content analysis techniques to identify concepts and relationships among variables. The findings indicate that the implementation of KBC-based quality management strengthens the quality culture of madrasahs through humanistic leadership, teacher professionalism development, collaboration among school stakeholders, and the internalization of values of love and responsibility in educational activities. The established quality culture promotes improved performance, commitment, and sustainable educational service quality, thereby supporting the realization of excellent, value-oriented, and competitive madrasahs.